Students' perceptions of autonomy-supportive versus controlling teaching and basic need satisfaction versus frustration in relation to life skills development in PE. (September 2019) - Cronin, Lorcan; Marchant, David; Allen, Justine; Mulvenna, Claire; Cullen, David; Williams, Gareth; Ellison, Paul
Abstract: Objectives: The aim of this study was to examine the relationships between perceived teacher autonomy support versus control and students' life skills development in PE, and whether students' basic need satisfaction and frustration mediated these relationships. Design: Cross-sectional study. Method: English and Irish students ( N  = 407, M age = 13.71, SD  = 1.23) completed measures assessing perceived autonomy-supportive and controlling teaching, basic need satisfaction and frustration (autonomy, competence, and relatedness), and life skills development in PE (teamwork, goal setting, social skills, problem solving and decision making, emotional skills, leadership, time management, and interpersonal communication). Results: On the bright side of Self-Determination Theory (SDT), correlations revealed that perceived teacher autonomy support was positively associated with students' basic need satisfaction and life skills development in PE. On the dark side of SDT, perceived controlling teaching was positively related to students' basic need frustration, but not significantly related to their life skills development. Mediation analyses revealed that autonomy and relatedness satisfaction mediated the relationships between perceived teacher autonomy support and students' development of all eight life skills. Competence satisfaction mediated the relationships between perceived teacher autonomy support and students' development of teamwork, goal setting, and leadership skills. Conclusions: Our findings indicate that satisfaction of the needs for autonomy, competence, and relatedness are important mechanisms that in part explain the relationships between perceived teacher autonomy support and life skills development in PE. Therefore, teachers may look to promote students' perceptions of an autonomy-supportive climate that satisfies their three basic needs and helps to develop their life skills. Highlights: Students perceived they developed life skills through physical education. Perceived teacher autonomy support was associated with students' life skills development. Basic need satisfaction was related to the development of students' life skills. Controlling teaching was only associated with students' basic need frustration.